Ruang Lingkup Difusi Inovasi Pendidikan - Chandra Gumilar; Ahmad Thoriq; Muhammad Mardiyansah (Lembaga Pengembangan Kinerja Dosen, 2025)
This study discusses the scope of innovation diffusion in education in Indonesia. In essence, education plays a fairly essential role in shaping the quality of human resources that are able to face the challenges of the times. Along with global changes marked by technological developments and economic transformation, demands on the education system continue to increase. The researcher uses a Qualitative Literature Review which is carried out by the researcher reading and observing various written reference sources related to the scope of innovation in education in Indonesia. The results of this study indicate that overall, the process of innovation diffusion in education involves various complex stages and requires support from all parties involved in the education system. Diffusion of educational innovation in general can be concluded as a very complex process and is influenced by various specific factors, both internally and externally in the educational environment.